Novel Histologic Finding: Adipose Tissue Is Prevalent Within Penile Tunica Albuginea and Corpora Cavernosa. (November 2017) - Rodriguez, Ingrid M.; Cuevas, Martin; Silvero, Arturo; Cañete-Portillo, Sofía; Sanchez, Diego F.; Barreto, Jose; Cubilla, Antonio L.
Abstract : Adipose tissue, along with arteries, veins, and peripheral nerves, is a normal constituent of mesenchymal tissues encasing the corpora cavernosa at the level of the penile shaft, variously designated as penile fascia or Bucks fascia. To our knowledge, the presence of fat has not been previously reported within the corpora cavernosa. One or 2 transversal histologic sections at the level of the surgical margin at the shaft of 63 consecutive partial penectomy specimens for squamous cell carcinoma were evaluated. From outer to inner tissues, 3 anatomic levels were identified: (1) outer fascia composed of a loose fibrovascular mesenchyme containing some nerve branches. Adipose tissue was present in the majority of the cases. (2) The tunica albuginea, a thick and dense fibroelastic band of tissue separating the outer fascia from the erectile tissues of the corpora cavernosa. Adipose tissue within the albuginea was present in 21 specimens (19%). (3) Erectile tissues of corpora cavernosa. Besides the typical erectile tissues, adipose tissue was present in 33 cases (52%). The fatty tissue was focal or multifocal and scant and peripherally located at the junction of the tunica albuginea with the corpora. In some cases, it was associated with small amounts of fibrous tissue, small vessels, and nerves. We are reporting the presence of adipose tissue in the tunica albuginea and the corpora cavernosa. It is possible that adipose tissue, along with small nutritional vessels and nerves perforates from the fascia, in which fat is usually present, through the tunica albuginea to reach the corpora. In a previous examination of the local routes of cancer spread, we found this pathway to be one of the mechanisms of cancer invading the penile corpora from the penile fascia.